Math, asked by writetomanojgupta, 10 months ago

2(5y-3) -3(2y -1) = 9
value of y = ?
show explanation​

Answers

Answered by Anonymous
2

\huge{\underline{\color{purple}{\mathfrak{Answer:}}}}

2 (5y - 3) - 3 (2y - 1) = 9

10y - 6 - 6y + 3 = 9

4y - 3 = 9

4y = 9 + 3

4y = 12

y =\dfrac{12}{4}

y = 3

__________________________

Answered by studyloveinfinity
0

Answer:

Y=3

Step-by-step explanation:

2(5y-3) -3(2y -1) = 9

=10y-6-6y+3=9

=4y-3=9

4y=9+3

4y=12

THEREFORE Y=12÷4=3

Similar questions